2006
DOI: 10.1128/aem.01029-06
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Escherichia coli Genotypes and Antibiotic Resistance Phenotypes in Feces of Humans, Cattle, and Horses

Abstract: Escherichia coli is the most completely characterized prokaryotic model organism and one of the dominant indicator organisms for food and water quality testing, yet comparatively little is known about the structure of E. coli populations in their various hosts. The diversities of E. coli populations isolated from the feces of three host species (human, cow, and horse) were compared by two subtyping methods: ribotyping (using HindIII) and antibiotic resistance analysis (ARA). The sampling effort required to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 32 publications
7
82
0
1
Order By: Relevance
“…Others have used a 2-enzyme digest (Meays et al 2006), or separate ribotyping analyses with 2 different enzymes (Harwood et al 2003, Jenkins et al 2003, Jones et al 2006, to increase the potential diversity in ribopatterns. However, studies where DNA profiles from many isolates from an individual animal have been compared show saturations of diversity, or richness, at different numbers of profiles (Carson et al 2001, Johnson et al 2004, McLellan 2004, Anderson et al 2006. Myoda et al (2003) suggested DNA banding patterns produced by ribotyping and other genotypic methods are probably random with respect to what makes individual and hostspecific strains of target bacteria unique, so the added cost of using a second enzyme may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have used a 2-enzyme digest (Meays et al 2006), or separate ribotyping analyses with 2 different enzymes (Harwood et al 2003, Jenkins et al 2003, Jones et al 2006, to increase the potential diversity in ribopatterns. However, studies where DNA profiles from many isolates from an individual animal have been compared show saturations of diversity, or richness, at different numbers of profiles (Carson et al 2001, Johnson et al 2004, McLellan 2004, Anderson et al 2006. Myoda et al (2003) suggested DNA banding patterns produced by ribotyping and other genotypic methods are probably random with respect to what makes individual and hostspecific strains of target bacteria unique, so the added cost of using a second enzyme may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons of Escherichia coli populations in various host animals are rare in the literature, as most studies have focused on one host species (Anderson et al 2006). No prior studies have specifically compared E. coli isolates between gull species or between more than one gull species and multiple environmental sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the percentages of resistance for cephalothin observed in this research were relevant. All these aspects should be highlighted, since few authors have investigated the presence of resistant bacteria in groundwater [19]. …”
Section: Figure 1: the Principal Components Obtained For The Bacteriamentioning
confidence: 99%
“…Library-dependent methods rely on the collection of FIB isolates from a known source for comparison of genetic or phenotypic patterns (fingerprints) of isolates from environmental samples. Such libraries are relatively location specific, and their utility is greatly hampered by the diversity and temporal variability of faecal organisms (Gordon 2001;Wiggins et al 2003;Anderson et al 2006).…”
Section: Introductionmentioning
confidence: 99%